Viral Ribonucleic Acid Shedding and Transmission Potential of Asymptomatic and Paucisymptomatic Coronavirus Disease 2019 Patients. (8th December 2020) - Samaddar, Arghadip; Gadepalli, Ravisekhar; Nag, Vijaya Lakshmi; Misra, Sanjeev; Bhardwaj, Pankaj; Singh, Pankaj; Meena, Mahadev; Sharma, Prem Prakash; Grover, Malika; Kumar Garg, Mahendra; Chauhan, Nishant Kumar; Dutt, Naveen; et al.
Abstract: We studied the pattern and duration of viral ribonucleic acid (RNA) shedding in 32 asymptomatic and 11 paucisymptomatic coronavirus disease 2019 cases. Viral RNA shedding in exhaled breath progressively diminished and became negative after 6 days of a positive reverse-transcription polymerase chain reaction test. Therefore, the duration of isolation can be minimized to 6 days.